The Emoji that Cost $20,000: Triggering Liability for Defamation on Social Media - Nicole Pelletier (Washington University Journal of Law & Policy, 2016)
This Note addresses the history of social media law in the U.S. legal system within the context of defamation claims and legislative acts to immunize social media websites. Using a British court’s finding of liability based on a tweeted emoji, Pelletier analyzes whether an emoji could trigger liability in the United States and juxtaposes the potential for individual user liability based on an emoji with the immunization granted to social media websites. Pelletier proposes new federal legislation that will place responsibility on social websites to notify users of potential liability arising from social media use.
Keywords: social media; emoji; liability; Computer Fraud and Abuse Act; Communications Decency Act; defamation; immunity; British court; Internet; U.S. legal system